Preparation and characterization of titanium dioxide nanoparticles and thin films - Liew, Sieng Ling (Universiti Malaysia Sarawak (UNIMAS), 2007)
Titanium dioxide (TiO2) nanoparticles in the form of colloidal suspension were prepared by three different synthesis approaches. These TiO2 sols were characterized using Scanning Ultraviolet-Visible Spectrophotometer to investigate their stability and relative aggregate sizes upon aging. TiO2 sol synthesized by method 1, (sol-gel method) was comparatively more stable than that of the other two methods. TiO2 thin films prepared under ambient temperature and after annealed at 400oC were porous and nanoparticulate in nature, with TiO2 nanoparticles of spherical shape. TiO2 films showed high hydrophilicity when the film was being exposed to sunlight. Ceramic tiles coated with TiO2 thin film were evaluated for their photocatalytic activities. However, no conclusive result was obtained in this study due to too short experimental duration.